Arturo Rodriguez, April 2001, Cesar Chavez Commemoration (2001)
[00:00:15] Footage begins. [00:00:31] Introduction for Arturo Rodriguez. [00:05:27] Arturo Rodriquez takes the podium. [00:05:35] Arturo Rodriquez speech begins with opening remarks. [00:07:42] The celebration of Cesar Chavez Day. [00:18:56] The failure of prior Farm Working Unions. [00:19:57] The beginning of the movement in Delano. [00:22:37] The Philosophy of Non-Violence. [00:24:50] Marching from Delano to Sacramento; SÍ se puede. [00:26:30] Major breakthroughs in the movement. [00:27:57] California Agricultural Relations Act (ALRA). [00:29:40] 'What is the United Farm Workers today?' [00:31:51] National Farmworkers Service Center. [00:32:51] The importance of communications. [00:35:00] Starting the first radio station for Farm Workers and bringing about social change. [00:39:30] Other non-profit organizations regarding Farm Workers. [00:41:20] Continuing United Farm Workers after Cesar Chavez's death. [00:45:10] Recent successes within the movement in developing relationships with employers. [00:55:36] Concluding remarks. [00:56:38] Questions and Answers with the audience. [01:19:20] Final comments. [01:20:55] Footage ends.